PROBLEMATIKA PELAKSANAAN PEMBELAJARAN TEMATIK PADA SDN GUGUS 7 KECAMATAN PUJUT TAHUN AJARAN 2019/2020 - Rahimayatul Aini; Ida Ermiana; Lalu Hamdian Affandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
The problem of implementing learning at SDN Cluster 7, Pujut District is very complex. Some of the problems that occurred were: difficulties in the assessment process; limited creativity of teachers; the use of learning media that is less than optimal; and various other problems. Therefore, in this study, we will raise a problem with the title